Pertanggungjawaban Pidana Bagi Pelaku Penyebaran Video Yang Memiliki Muatan Pencemaran Nama Baik Melalui Media Sosial - Rohna Syukriaty Kaloko (Iuris Studia: Jurnal Kajian Hukum, 2023)
The main issue is regarding criminal elements in the imposition of criminal sanctions on perpetrators of distributing videos containing defamation via social media. This is because the article on criminal defamation through social media requires that the party who can be punished is the party who distributed the video and not the party who made the video. One of the acts of defamation through social media that has occurred is stated in the Sibolga District Court Decision Number 176 Pid.Sus/2019/PN.Sbg. Based on the research results, it is known that the factors involved in committing acts of defamation through social media can be seen from political factors, economic factors and socio-cultural factors which can be seen from the aspect of advances in information technology, human resources and from the aspect of new communities on social media. Regulation of criminal sanctions for perpetrators of distributing videos containing defamatory content via social media in the form of imprisonment for a maximum of 4 (four) years and/or a fine of a maximum of Rp. 750,000,000.00 and the offense used is the offense of complaining. It is known that based on the results of the legal analysis of the Sibolga District Court Decision Number 176 Pid.Sus/2019/PN.Sbg, there were errors made by the judge in the first decision in terms of the legal subject of the main perpetrator carrying out the distribution not being involved and in terms of the criminal sanctions being too light given to the perpetrator, even though the impact of his actions was very broad and detrimental to the victim whose reputation was defamed.